2014
DOI: 10.1073/pnas.1316006111
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling disagreement over climate–conflict results in Africa

Abstract: Significance Whether climatic changes affect civil conflicts has been the subject of intense academic debate. Much of this controversy originates from a highly cited dispute between a previous PNAS paper—which finds that civil war incidence in sub-Saharan Africa is associated with increasing local temperature—and a subsequent rebuke of this result, also published in PNAS. We reexamine this apparent disagreement by comparing the statistical models from the two papers using formal tests. When we implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…The question whether or not climate-related factors have significantly contributed to recent armed-conflict outbreaks has been heavily disputed in the scientific literature (33)(34)(35)(36)(37)(38). Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question whether or not climate-related factors have significantly contributed to recent armed-conflict outbreaks has been heavily disputed in the scientific literature (33)(34)(35)(36)(37)(38). Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43). Other literature that assessed the influence of climate signals on armed-conflict outbreak risk did not report a robust connection (9,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…A household's water needs not being met can negatively impact their desire to undertake conflict activities in pursuit of water resources, opting instead to maintain collaborative relationships [50]. Needs not being met may also positively impact the potential for conflict activities in pursuit of water [5,18,29]. Percentage of households reporting whether their crop and household water needs and crop water needs were met over the past ten years, last year, and if they thought they would be met next year.…”
Section: Independent Variables Used In the Modelmentioning
confidence: 99%
“…However, the relationship between climate change, water insecurity, and human conflict is a much-debated topic [3][4][5][6][7]. The potential impacts of climate change on agriculture, water scarcity, and human security are especially worrisome for rain fed subsistence farmers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Burke et al (2010) concede that the relationship weakens over time, rejecting the other criticisms [26]. The debate has since resurfaced with Hsiang and Meng (2014) holding that there was agreement on an effect of temperature [27] with Buhaug (2014) disagreeing [28]. Commentators argued that disciplinary modeling traditions could explain some differences [29].…”
Section: The Climate-conflict Debate Pre-2014mentioning
confidence: 99%